Design of an IoT-Based Heart Rate and Room Temperature Monitoring System Using ESP32 - Peter Simanjuntak; Muhammad Imam Zarkasyi (Universitas Satya Terra Bhinneka, 2026)
Introduction/Main Objectives: Continuous monitoring of heart rate and environmental conditions is essential for supporting remote healthcare services and real-time observation. This study aims to design and implement an Internet of Things (IoT)-based monitoring system using ESP32 for simultaneous monitoring of heart rate, room temperature, and humidity. Background Problems: Conventional monitoring systems generally require separate devices for physiological and environmental measurements and provide limited remote monitoring capabilities. Therefore, there is a need for an integrated, low-cost, and real-time IoT-based monitoring system. Novelty: The proposed system integrates a pulse heart rate sensor and a DHT11 temperature-humidity sensor into a single ESP32-based IoT platform. The system incorporates Wi-Fi communication, cloud-based visualization using the Blynk platform, and a finger-detection mechanism to minimize false heart rate readings caused by sensor noise. Research Methods: The system was developed using an ESP32 microcontroller, a pulse heart rate sensor, and a DHT11 sensor. Sensor data were acquired, processed, and transmitted through a Wi-Fi network to the Blynk cloud platform for real-time visualization. Experimental evaluation was conducted in a laboratory environment under three operating conditions: Danger, Normal, and Not Detected. Finding/Results: The experimental results demonstrate that the proposed system successfully monitored heart rate, room temperature, and humidity in real time. The system accurately classified monitoring conditions into Danger, Normal, and Not Detected states. Furthermore, the implemented finger-detection mechanism effectively prevented false heart rate measurements when no finger was placed on the sensor, while maintaining stable wireless communication and continuous cloud-based monitoring. Conclusion: The proposed ESP32-based IoT monitoring system provides a practical, low-cost, and reliable solution for integrated physiological and environmental monitoring. The successful implementation demonstrates the feasibility of using ESP32 as an IoT gateway for real-time health monitoring applications, particularly for educational purposes, laboratory experiments, remote monitoring, and prototype smart healthcare systems.